Converter Technology in Cascade Control System - ZHANG Xingqi; LUO Min; REN Kaichun; ZHANG Xiaochun; ZHANG Qian (Kongzhi Yu Xinxi Jishu)
Cascade control used in high-voltage and large-capacity winding motor speed adjustment is a high efficient and stable method, and the converter technology directly determines the speed adjusting performance of cascade control system. By studying on the cascade control systems consist of different converters, it has certain significance to improve the design of the cascade control system and to promote the development of the converter technology.